The Importance of Implementing HR Best Practices in regard to Starbucks Employee Performance in Surabaya with Job Satisfaction as the Mediator - Celine Setiawan; Osawa Yukari (iBuss Management, 2023)
Nowadays, in a dynamic business environment, employee performance is a crucial aspect of an organization’s development and for it to remain sustainable in the future. To achieve this situation, HR best practices must be implemented to support a healthy working environment, eventually boosting employees’ job satisfaction. Employees who feel pleased with the organization they are working at become encouraged to perform well and excel in their job. This research will perform a study on the connection between variables like HR best practices regarding training and development, rewards and compensation, employee empowerment, and performance appraisal toward job satisfaction. In addition, this research will examine whether job satisfaction has a mediating influence on HR best practices and employee performance regarding Starbucks employees in Surabaya. The data were gathered by utilizing the purposive sampling technique. A mixture of personally administered and online questionnaires was used for collecting data from 65 respondents. To understand and interpret the data, PLS-SEM was implemented. Results show that all HR best practices except rewards and compensation significantly relate to job satisfaction. Moreover, job satisfaction has mediating effects on all HR best practices except for rewards and compensation on employee performance. Furthermore, limitations and future directions are shown in the end. Keywords: job satisfaction, training and development, rewards and compensation, employee empowerment, performance appraisal, employee performance, Starbucks, Surabaya.